INTERNALISASI NILAI-NILAI ISLAM DALAM IBADAH MAHDHAH BAGI SISWA MADRASAH TSANAWIYAH NURURRODIYAH KOTA JAMBI - Marsyalena, Rika; Saputra, Edi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of instilling Islamic values in shaping students' religious character, especially through mahdhah worship in the madrasah environment. In practice, worship activities such as congregational prayers and Quran recitation have indeed been carried out, but there are still students who perform them merely as an obligation without understanding the meaning contained within. This indicates that the process of internalizing Islamic values has not yet been fully optimized. Therefore, this research aims to understand how the process of internalizing Islamic values, the supporting and inhibiting factors, as well as the strategies used to strengthen this internalization at MTs Nururrodiyah Kota Jambi. This research uses a qualitative approach with a case study type. Data were obtained through observation, interviews, and documentation involving PAI teachers, the head of the madrasah, and students as research subjects. The data were analyzed through the stages of reduction, presentation, and conclusion drawing, and their validity was tested thru triangulation. The research results show that the internalization of Islamic values is carried out thru the habituation of worship, the exemplary behavior of teachers, and the support of a religious madrasah environment. The supporting factors include the role of teachers, adequate facilities, and school culture, while the obstacles include the lack of student awareness, external environmental influences, and limited supervision outside of school. Thus, cooperation between the school and parents, as well as consistent habituation, is necessary so that Islamic values can be well instilled in the students.